Interaction Imperatives EEMA, SCO and BRICS in Global Geopolitics - I. F. Kefeli (Евразийская интеграция: экономика, право, политика, 2019)
Analyses the processes of global geopolitical and economic integration in the Eurasian space. The CSTO is regarded as a shield EEMA growing arc of instability. Determined the imperatives of interaction EEMA, SCO and BRIC and scenarios for development of the Eurasian civilization.